(untitled) (diségno, 2024)
The construction details presented during the XII Milan Triennale in 1960 and at the Venice Architecture Biennale in 1968 suggest that Franco Albini and Franca Helg employed the mock-up as a tool to evaluate innovative solutions in the realization of the Nuova Rinascente in Piazza Fiume, Rome, inaugurated in 1961. Faced with regulatory constraints and contingent factors, the architects explored various project possibilities. It is noteworthy that the transition from an initial design (1957), characterized by steel portals and travertine walls, to the completed project (1961), featuring a steel frame and exterior closure in Silipol panels, is primarily attributed to an imposition by the Superintendency which required a ‘Roman’ character for the building. Consequently, the ‘ostentatiously two-dimensional’ front of the initial project had to change into a ‘corrugated surface’ of panels, leading the architects to conceive a prefabricated version of the traditional stone facade. By reconstructing the ideational process of the Nuova Rinascente project in Rome, this contribution aims to explore the architect-engineer’s general inclination to experiment, through the mock-up, with an ‘unconventional’ approach to design, conceived as the potential radicalization of new spatial, formal, and material protocols that require the precision of work as an essential prerequisite for the quality of outcomes.